The Flowering Thorn - McKean, Thomas (Utah State University, University Libraries, 2003)
The flowering thorn expresses the dual nature of the ballad: at once a distinctive expression of European tradition, but also somewhat tricky to approach from a scholarly perspective, requiring a range of disciplines to illuminate its rich composition. Most of this latter quality has to do with the very features that characterize ballads... or narrative songs. These include an appearance of fragmentation; a wide range of cultural and social referents; complex, evocative symbolic language; and variation. The notable multiformity of meaning, text and tune is mirrored in scholarship, too. The Flowering Thorn is therefore wide ranging, with articles written by world authorities from the fields of folklore, history, literature, and ethnology, employing a variety of methodologies